Unsung land, aspiring nation : journeys in Bougainville - Peake, Gordon P. (Gordon Patrick), 1973- (Pacific series., 2022)
In 2016, Gordon Peake answers a job advertisement for a role with the government of the Autonomous Region of Bougainville, a collection of islands on the eastern fringe of Papua New Guinea looking to strike out as a country of its own. Blending narrative history, travelogue and personal reminiscences, Unsung Land, Aspiring Nation is an engaging memoir as well as an insightful meditation on the realities of nation-making and international development.